A detachable chain tensile energy absorber inspired by mortise and tenon joint. (1st June 2022) - Zhou, Sicong; Liu, Hua; Li, Bo; Yang, Xianfeng; Yang, Jialing
Highlights: A novel detachable chain tensile energy absorber (DCTEA) is designed. The DCTEA has more stable deformation mode and no global buckling appears. SEA of the foams are 2.6 times higher in DCTEA than in unconstrained compression. The DCTEA filled with density-gradient foams have a multi-stage deformation mode. The DCTEA can be designed into a variety of cross-sectional shapes and multi-chain. Abstract: Due to inherently mechanical behavior, the long porous structures may inevitably result in global buckling under compression, which is adverse to absorbing the impact energy. To make the material completely crushing, this paper proposes a novel detachable chain tensile energy absorber (DCTEA) inspired by mortise and tenon joint, which consists of chain structures and aluminum foams. The aluminum foam filled in the chain structure is used to absorb the impact energy while the chain structure can prevent global buckling. The quasi-static compression tests are conducted to determine the constitutive relationship of aluminum foams with different densities, and the tensile tests by using the DCTEA are carried out to study the mechanical properties and energy absorption capacity. Besides, the numerical model is established by LS-DYNA, and the elastic-plastic material model is used for the chain structure while the Deshpande-Fleck foam model is applied to the aluminum foams. Compared with the unconstrained compression, the aluminum foams in the DCTEA have more stable energy absorption mode and no global buckling appears during the deformation process. In addition, specific energy absorption (SEA) of the aluminum foams in the DCTEA increases by 160.2% compared with those under unconstrained compression. The quasi-static tensile mechanical responses of the DCTEA filled with density-gradient aluminum foams are also studied, and the energy absorption process can be regulated by adjusting the density distribution of the aluminum foam cores. The DCTEAs with different cross-sectional shapes and chain numbers can be designed according to different application scenarios. Graphical abstract: Image, graphical abstract